Prognostic value of postdiagnostic inflammation-based scores in short-term overall survival of advanced pancreatic ductal adenocarcinoma patients. Issue 50 (December 2017) - Xiao, Yuanyuan; Xie, Zhihui; Shao, Zhenyi; Chen, Wen; Xie, Hua; Qin, Guoyou; Zhao, Naiqing
Abstract : Abstract: The prognostic relevance of commonly used composite inflammation-based scores remains severely underdiscussed in pancreatic cancer (PC), especially for advanced PC. In this retrospective cohort study, we aimed to discuss the association between multiple inflammatory scores and the short-term overall survival (OS) of advanced pancreatic ductal adenocarcinoma (PDAC) patients. A total of 66 histologically confirmed PDAC patients were retrospectively analyzed. A multivariate Cox proportional hazards model was used to explore the association between 6 commonly used inflammatory scores measured right after diagnosis, Glasgow Prognostic Score (GPS), Modified Glasgow Prognostic Score (mGPS), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), prognostic index (PI), prognostic nutritional index (PNI), and the short-term OS of advanced PDAC. Analytical results revealed that among GPS, mGPS, NLR, PLR, PI and PNI only PLR was significantly associated with short-term OS of PDAC. For both 1-year and 2-year OS, every 10 increase of PLR value resulted in 1.10 (95% CI: 1.04, 1.16) folds hazard ratio (HR). Further analysis identified a statistically significant dose–response relationship between PLR and HR. Our study results probably suggested that PLR is a promising prognostic factor of advanced PDAC; maintaining normally ranged platelet count may gain short-term survival benefit among such patients.